The Mediation Agreement in the Light of the New Legal Regulations - IGNAT, Claudiu (Journal of Advanced Research in Law and Economics, 2019)
One of the purposes of the mediation procedure, when the parties have cooperated constructively reaching an agreement, is the mediation agreement. This manner to settle amicably a conflict, gives the parties involved in the mediation procedure, a concrete opportunity to establish with rules and time delivery and implementation of the agreement negotiated by means of the mediator.